Soft discernibility matrix and attribute reduction for information systems - YAN De-qin1; LI Ke-qiu2; CHI Zhong-xian2 (Tongxin xuebao)
A new concept of soft discernibility matrix was proposed, and related theorems were given. By using soft discernibility matrix,attribute reductions of incomplete information systems, fuzzy value information systems and vague sets value information systems were realized. The research results provide a way to study soft discernibility matrix for real value information systems. The new concept and related methods for attribute reduction are further development to the theory and applications of rough sets.